Analysis Vulnerability Disaster of Landslide in Lantan Village Using Geoelectric Data and Sentinel Image - Syarifatul Ulfah; Adi Susilo; Marzuki Marzuki (Jurnal Penelitian Pendidikan IPA, 2021)
The vulnerability of landslides in Lantan Village, North Batukliang District, Central Lombok Regency has been analyzed using geoelectric data, rainfall, soil movement, and topographic slope. Resistivity data was acquired by the G-Sound resistivity meter using the dipole dipole configuration method and visualized using the RockWorks15 software. We also used rainfall data and ground movement data.  The ground movement was estimated from Sentinel-1A satellite data, processed using the DInSAR (Differential Interferometry Synthetic Aperture Radar) method. The slope data was obtained based on the topographic slope map of the Central Lombok Regency. The results showed that the slip surface was indicated to be located in silt clay with sand and the direction of the landslide in the study area was to the northwest with the type of landslide that might occur was a type A translational landslide. The depth of the slip surface varies from 1.5 m to 21.5 m.  The average monthly rainfall varies from low to high (<100 – 300 mm) with a monsoon rain pattern. Land movement in the form of land subsidence was observed at a rate of -0.27 to -0.30 cm/year during 2018 - 2020, with average land subsidence of -0.285 cm/year. The potential for landslides is also seen from the slope value of 40°, which is categorized as very steep. With all these conditions, the level of vulnerability to landslides in Lantan Village is high, and hopefully, the results of this study can be a reference for related parties in making efforts to minimize the impact of this disaster.